Pengaruh Media Loose Part Terhadap Peningkatan Kreativitas Anak Usia 5-6 Tahun Di TK GKPI Tarutung Kota - Resti Dama Yanti Amazihono; Adiani Hulu; Winarti Agustina Siahaan (Universitas Katolik Widya Karya Malang, 2023)
The researcher found a problem in class B5 TK GKPI Tarutung Kota, out of 10 children, 70% of children had low creativity when making initial observations. The purpose of this study was to determine the effect of Loose Part media on increasing the creativity of children aged 5-6 years at TK GKPI Tarutung Kota. This research is a quantitative research with a pre-experimental design, the research formula is One-group-pretest-posttest. The population in this study was 110, namely all children aged 5-6 years at TK GKPI Tarutung Kota. Sample A total of 25 children, the sample was selected using the Non-Random Sampling method with Purposive Sampling technique. Data were collected using interview guide sheets and observation sheets based on the observation rubik. The results of data analysis show that Loose Part media can increase the creativity of children aged 5-6 years at TK GKPI Tarutung Kota. The average value of children's creativity before treatment was 4.32 and after treatment was 9.00. After calculating the t-test, the tcount value is 15.396 where the tcount value is greater than ttable. So that the tcount value is 15.396 > ttable 2.064. So it can be concluded that Ho is rejected and Ha is accepted.